TANAMAN POTENSIAL PENYERAP LIMBAH STUDI KASUS DI PULAU BATAM - Sabaruddin Wagiman Tjokrokusumo (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2003)
Industrial development has resulted in increasing population growth and their activities in Batam Island. Increasing growth of industrial activities and human population has a direct impact on increasing water demand and water pollution, especially on surface water resource degradation. However control on this type of problem has not been done properly due to lack of awareness and environmental knowledge. To protect and conserve water resources from pollution and degradation, some activities have to be done in the future to protect water quality and quantity. Aquatic plants have ability to improve water quality to assimilate and transform pollutants into plant tissue and sedimentation process. Based on flora and fauna biological survey, the recent study found that some aquatic plants were observed has a potential and ability to absorb and uptake nutrient and pollutants. Those important plants are Rynchospora sp., Scleria sp., Cyperus sp., Hypolythrum sp., and Fimbristylis sp.